False Positive 18F-FDG Uptake in Mediastinal Lymph Nodes Detected with Positron Emission Tomography in Breast Cancer: A Case Report - Gamze Uğurluer; Mustafa Kibar; Sinan Yavuz; Akin Kuzucu; Meltem Serin (Case Reports in Medicine)
Breast cancer is the most frequently diagnosed cancer among females. It is accepted that lymph node involvement with metastatic tumor and the presence of distant metastasis are the most important prognostic factors. Accurate staging is important in determining prognosis and appropriate treatment. Positron emission tomography with computed tomography detects malignancies using 2-[18F]-fluoro-2-deoxy-d-glucose (18F-FDG PET CT) with high accuracy and they contribute to decisions regarding diagnosis, staging, recurrence, and treatment response. Here, we report a case of false positive metastatic mediastinal lymph nodes that were diagnosed by 18F-FDG PET CT in a 40-year-old breast cancer patient who had undergone preoperative evaluation. Right paratracheal, prevascular, aorticopulmonary, precarinal, subcarinal, hilar, and subhilar multiple conglomerated mediastinal lymph nodes were revealed in addition to left breast mass and axillary lymph nodes. Mediastinoscopy was performed with biopsy and pathology was reported as granulomatous lymphadenitis. In conclusion, any abnormal FDG accumulation in unusual lymph nodes must be evaluated carefully and confirmed histopathologically.